Assessment of General Dentists' Knowledge of the new Classification of Periodontal and Peri‐implant Diseases and Conditions 2017: A Cross-Sectional study in Saudi Arabia - Abdullah Saleh Almutairi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The most widely accepted and used classification in the periodontics field was that of the World Workshop 1999. However, due to several shortcomings, in 2018 the World Workshop devised a new classification for periodontal and peri-implant diseases and conditions. This study aims to explore general dentists’ knowledge about the new Classification of Periodontal and Peri‐implant Diseases and Conditions 2017. Methods: A cross-sectional web-based questionnaire-based study was conducted from December 2020 to May 2021 targeting Saudi Arabian primary care dentists. The sample size was 242 participants and after written informed consent, they were given web-based questionnaires consisting of 20 questions to complete. The study protocol was explained to the participants. Result: Of 310 dentists, 242 agreed to participate, with a response rate of 78.06%. The results showed that 143 participants (59.1%) were aware of the new classification while the rest were not. Half of the participants used it (50%), whereas the rest either did not use it or chose “not applicable.” Participating male dentists had more knowledge of the classification than female dentists (P <0.001). Dentists graduating after 2018 and those who graduated from governmental college knew more about the new classification than those who had graduated from private colleges. Conclusion: In this study, a moderately low percentage of participants displayed either no awareness of this new periodontal classification or did not use it, especially the graduates before 2018. Hence, there is an urgent need to spread awareness of the new classification among the dental community since it is a clinical and treatment-based classification.